Barriers to oral health care service utilization in Awo-Gareji community, Ankpa Local Government Area, Kogi State, Nigeria - Omale, Dr. Johnson J.; Hussain, B. M.; Nweze, M. C.; Ani, S. A.; Ohadoma, A. N. (Orapuh Journal, 2025)
Introduction Lack of access to oral health care can result in delayed diagnosis, untreated oral diseases, compromised health status, and, occasionally, death. People who have access to oral health care services are more likely to receive basic preventive care and education on personal behavioural modifications. Purpose This study investigates the barriers to utilizing oral health care services in Awo-Gareji community, Ankpa LGA, Kogi State, Nigeria. Methods A cross-sectional survey research design was adopted for this study. A total of 399 adults in the community were meant to participate; however, 200 respondents who expressed interest in the study (through verbal consent) were conveniently selected from a population of over 2,000 adults. The instrument for data collection was a structured questionnaire, similar to those used by other authors but with slight modifications. Results Oral health problems among the respondents included deposits such as dental plaque (15; 7.50%), stains (12; 6.00%), and dental calculus (9; 4.50%). Dental disease conditions reported included dental caries (10; 5.00%), gingivitis (70; 35.00%), and periodontitis (21; 10.50%). Other oral health problems identified were fractures (2; 1.00%), abrasion (19; 9.50%), attrition (40; 20.00%), and erosion (2; 1.00%). The study also revealed that awareness of the availability of oral health care services was significantly low among the respondents, with 89 (44.50%) unaware of such services, while only 60 (30.00%) were aware. Regarding barriers to the utilization of oral health care services, 62 (31.00%) of respondents identified the unavailability of a dental clinic in the community as the primary barrier. Additionally, 46 (23.00%) cited a lack of funds as a serious challenge, while 40 (20.00%) reported a lack of awareness about the importance of oral health care as a barrier. A few respondents (5; 2.50%) identified the high cost of dental treatment as a limiting factor. The hypothesis test results showed that the p-value was 0.073756, indicating that barriers to the utilization of dental services exist among the community members. Conclusion Oral health awareness should be promoted in rural areas, and state and local governments should integrate dental health services into existing primary health care centres.